Analisa Kebutuhan Pembelajaran Mata Kuliah Bahasa Inggris untuk Mahasiswa Non-Jurusan Bahasa Inggris di Universitas Islam - Alfian Alfian (INNOVATIO: Journal for Religious Innovation Studies, 2019)
The purpose of this study is to analyze the needs of students towards English courses for non-English Department students. This research is focused on analyzing the need for teaching materials, desired teaching methods and student language learning strategies. This research is a case study involving 136 Islamic Religious Education (PAI) and Islamic Religion Teacher Education (PGMI) students. The data was collected from respondents by conducting surveys and interviews. Survey data were analyzed using SPSS and Thematic analysis was used to analyze data from interviews. The results of this study indicateed that speaking skill is the skill that is mainly needed by students. Furthermor the development of vocabulary is also the main focus of the students. The results of this study with regard to learning methods show that students like mixed methods. In reference to the learning strategy, the students used variety and wide range of learning strategies. This research is very useful for English language teachers especially for the preparation of the lesson plan for non-English major students.